PENGARUH KEGIATAN EKSTRAKURIKULER PRAMUKA TERHADAP PEMBENTUKAN KARAKTER KEDISIPLINAN PESERTA DIDIK DI SMA NEGERI 1 PERANAP - Melcin, Sella Angelina; Hambali, Hambali; Radini, Radini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the declining level of discipline among students at SMA Negeri 1 Peranap, as indicated by behaviors such as arriving late, skipping school, not submitting assignments on time, and violating school regulations. Scouting extracurricular activities should contribute to the formation of students' disciplined character. Therefore, this study aims to determine the effect of scouting extracurricular activities on the formation of students' disciplined character at SMA Negeri 1 Peranap. This study uses a quantitative approach. Data were collected by distributing questionnaires to 48 students who actively participate in scouting extracurricular activities, consisting of 29 statement items, to obtain data on variables X and Y. The sample was determined using a total sampling technique. Data were analyzed using simple linear regression in SPSS version 27. The results showed that scouting extracurricular activities had a positive effect on students' disciplined character. This is known from the simple linear regression equation, which yields Ŷ = 26.854 + 0.307X, indicating that an increase in scouting extracurricular activities is followed by an increase in student discipline. The results of the F test show that the F count (6.461) is greater than the F table value (4.052); thus, the research hypothesis is accepted. In addition, the coefficient of determination (R²) value of 0.123 indicates that scouting extracurricular activities account for 12.3% of the variation in student discipline character, while the remaining 87.7% is influenced by other factors outside the scope of this study.